Cobalt Extraction from Depleted Lithium-Ion Batteries and Its Leaching Kinetics - Alfred Obaje; Douglas Onyancha; Samuel Mirie (Recent Developments in Chemistry and Biochemistry Research Vol. 11, 2025)
Rechargeable batteries called lithium-ion batteries (LIBs) use the reversible reduction of lithium ions to store energy. Lithium-ion phosphate, lithium nickel oxide, lithium manganese oxide, and lithium cobalt oxide are among the different types of lithium batteries, making up the majority of LIBs cathode while LiNixCoyMnzO2 cathode material is commonly used in modern car batteries. Lithium-ion batteries are frequently employed as rechargeable batteries, driving most electronics and electric cars, significantly increasing the quantity of utilized LIBs. Hence, ecosystems may be threatened by these used LIBs, due to the presence of heavy metals and poisonous electrolytes. Hence, for sound protection and financial considerations, it is highly essential to develop an efficient method to recycle used LIBs with the aim of preventing hazardous compounds from entering the ecosystem endangering people’s health and recovering valuable metal. The study concentrated on cobalt recovery using hydrometallurgical and thermal treatment techniques that enhanced a high rate of recovery, low energy use, and less waste production. Used LIBs of mobile phones, were collected from phone repairing shops in Nyeri town, Keny = Hydrometallurgical process which involves acid leaching using mineral acids and organic acids was applied by using H2O2 as a reductant. Sodium chloride 4% wt. (of analytical grade) for discharging the batteries and sodium hydroxide 10% wt. (of analytical grade) for dissolution of aluminium foil charge collectors were prepared using deionized water. The leaching process was optimized by varying parameters (type of acid, acid concentration, reductant dosage, time, and temperature). Cobalt ion concentration level in liquor was analysed via ICP - OES, and finally cobalt was extracted from the leachate liquor via precipitation. XRF analysis showed that cathode active material has the highest composition of 61.72% cobalt and other valuable metals like 12.11%Ni and 9.64%Mn, hence is a need to recycle the cathode active material to recover the valuable metals and minimize chances of heavy metals release into the environment. Optimum conditions for leaching cobalt from cathode material were as follows: 80\(^°\)C, 120 minutes, 1.5%v/v of H2O2, for both 3M2SO4 and 2MC6H8O7 . The cobalt leaching followed the chemical reaction model, with the best satisfactory regression coefficient fitting values above 0.98 and activation energy as 21.84 and 7.89 kj/mol, and percentage recovery of 82.75% and 67.47% while using 3M2SO4 and 2MC6H8O7 respectively.